Cytokines in cutaneous lupus erythematosus. (August 2011) - Wittmann, Miriam; Goodfield, Mark
Clinical manifestations of cutaneous lupus erythematosus are diverse and different subtypes of the disease have been defined. It is characteristic for lupus skin inflammation that a significant activation of innate interferon pathways is observable. Endogenous molecules indicative for tissue damage (damage-associated molecular patterns [DAMPs]) show cytokine-like properties once released from intracellular compartments and these DAMPs have been shown to influence the course of inflammatory responses. Cytokines including TNF-αα and IL-1 family members significantly contribute to the chronic inflammatory phenotype and, in combination with DAMPs, impact on the activation of innate interferons. A better understanding of the deregulated cytokine network in cutaneous lupus erythematosus patients with distinct disease phenotypes and genetic backgrounds is of high importance and a prerequisite for recommending and developing more individualized therapeutic strategies.